Implementasi Kegiatan Melipat dan Menempel Origami dalam Mengembangkan Motorik Halus Anak di TK Aisyiyah Bustanul Athfal - Nadia Sabila Naibaho; Rizka Harfiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the implementation of folding and pasting origami activities in developing children's fine motor skills at TK Aisyiyah Bustanul Athfal. The research focuses on explaining teachers' pedagogical efforts, identifying supporting and inhibiting factors, and describing the developmental outcomes observed during the implementation process. This study employed a descriptive qualitative approach using participatory observation, semi-structured interviews, and documentation as data collection techniques. Data were analyzed through data condensation, data display, and conclusion drawing, supported by source and technique triangulation. The findings indicate that the implementation was carried out through structured pedagogical stages, including initial motor stimulation, step-by-step demonstrations, and individual assistance. Key supporting factors included the children's high enthusiasm for colorful media and teacher readiness, while inhibiting factors involved variations in initial motor readiness. The study highlights that the development of fine motor skills is closely related to the quality of pedagogical implementation and the consistency of stimulation provided through origami media.